Formulasi Lip Cream Mengandung Minyak Almond (Oleum amygdalae) sebagai Pelembab Bibir - Nurul Afifah Aprilia; Dina Mulyanti; Gita Cahya Eka Darma (Bandung Conference Series: Pharmacy, 2024)
Abstract. Lip cream is a lip makeup preparation, has a semi-solid shape that keeps lips moisturized longer. The use of natural moisturizing ingredients in lip cream preparations is currently starting to be in demand by consumers. One of the natural ingredients that has the potential to provide moisture is almond oil. This research aims to get the best formula for lip cream preparations that contain active substances in the form of almond oil. The thickener used is 15% microcrystalline wax. The use of almond oil is made with a wide variety of concentration variations starting from 60; 57,5; 55; 52,5; 50; and 47.5%. The evaluation was carried out on all lip cream formulas including organoleptis test, homogeneity test, pH test, dispersibility test, and viscosity test. The final evaluation of the preparation was carried out by a storage stability test at 4o and 40oC for 6 cycles and a moisture test using cobalt chloride paper. Based on the results of the evaluation, the selected formula is formula 4 with the characteristics of pink organolepstis, semisolid, homogeneous, pH 5, with a viscosity value of 4868 cp, and a dispersion of 5.8 cm, but it is unstable after storage stability testing. The humidity testing in this study is only qualitative, so it is necessary to develop a quantitative moisture test method, and it is necessary to develop a formula in the use of the right dye for the preparation. Abstrak. Lip cream merupakan sediaan riasan bibir, memiliki bentuk semisolid yang menjaga kelembapan bibir lebih lama. Penggunaan bahan pelembab alami pada sediaan lip cream pada saat ini mulai diminati konsumen. Salah satu bahan alami yang berpotensi memberikan kelembaban adalah minyak almond. Penelitian ini bertujuan untuk mendapatkan formula terbaik sediaan lip cream dengan mengandung zat aktif berupa minyak almond. Thickener yang digunakan adalah microcrystalline wax 15%. Penggunaan minyak almond dibuat dengan berbagai macam variasi konsentrasi dimulai dari 60; 57,5; 55; 52,5; 50; dan 47,5%. Evaluasi dilakukan terhadap seluruh formula lip cream meliputi uji organoleptis, uji homogenitas, uji pH, uji daya sebar, dan uji viskositas. Evaluasi akhir sediaan dilakukan pengujian uji stabilitas penyimpanan pada suhu 4o dan 40oC selama 6 siklus serta uji kelembaban dengan menggunakan kertas kobalt klorida. Berdasarkan hasil evaluasi formula yang terpilih adalah formula 4 dengan karakteristik organolepstis pink, berbentuk semisolid, homogen, pH 5, dengan besaran nilai viskositas 4868 cp, serta daya sebar sebesar 5,8 cm, namun tidak stabil setelah pengujian stabilitas penyimpanan. Pengujian kelembaban pada penelitian kali ini hanya bersifat kualitatif sehingga diperlukan pengembangan metode uji kelembaban secara kuantitatif, serta diperlukan pengembangan formula dalam penggunaan pewarna yang tepat untuk sediaan.